A relational study of the Black middle classes and globalised White hegemony: Identities, interactions, and ideologies in the United States, United Kingdom, and South Africa. Issue 9 (24th July 2017) - Meghji, Ali
Abstract: In this paper, I explore the experiences of the Black middle classes across the United States, United Kingdom (UK), and South Africa. I argue that the similar experiences the Black middle classes face across these nations are not coincidental but represent the process of globalised White hegemony. Globalised White hegemony refers to how the middle class, transnationally, is often understood as a symbolic category informed by specific White norms, identifications, and practices. I explore globalised White hegemony through three areas of Black middle‐class experience: identity, interactions, and ideologies. Thus, I examine how across the UK, United States, and South Africa, the Black middle classes construct public identities according to White norms, encounter interactions through which their blackness negatively trumps their middle‐class status, and confront classed‐racialised ideologies, which construe the Black middle class as inauthentic. I argue in this paper that central to fleshing out the similarities in Black middle‐class experiences across the globe is engaging in relational sociology, which stresses the globalised nature of contemporary raciality.